2017
DOI: 10.1002/ijc.31099
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐infiltrating tryptase+ mast cells predict unfavorable clinical outcome in solid tumors

Abstract: The prognostic role of tumor-infiltrating tryptase mast cells in human solid tumors remains controversial. Herein, we conducted a meta-analysis including 28 published studies with 4224 patients identified from PubMed and EBSCO to assess the prognostic impact of tumor-infiltrating tryptase mast cells in human solid tumors. We found that tryptase mast cell infiltration significantly decreased overall survival (OS) and disease-free survival (DFS) in all types of solid tumors. In stratified analyses, tryptase mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…factors [66]. Tryptase may activate the plasminogen activator and induce the release of VEGF and FGF-2 from their extracellular matrix-bound state [37]. Maniga et al reported the accumulation of MCs in tumors of breast cancer and that MC-derived tryptase is capable of initiating fibroblast differentiation and promoting stromal remodeling [17].…”
Section: And Extracellular Matrix During Tumor Developmentmentioning
confidence: 99%
“…factors [66]. Tryptase may activate the plasminogen activator and induce the release of VEGF and FGF-2 from their extracellular matrix-bound state [37]. Maniga et al reported the accumulation of MCs in tumors of breast cancer and that MC-derived tryptase is capable of initiating fibroblast differentiation and promoting stromal remodeling [17].…”
Section: And Extracellular Matrix During Tumor Developmentmentioning
confidence: 99%
“…Especially, a growing body of evidence indicates that mast cells are implicated in tumor development [68][69][70][71][72][73]. Indeed, these cells are known to favor immunologic tolerance and secrete both growth and angiogenic factors which enhance tumor expansion [74][75][76]. Notably, a positive effect of mast cells has been observed on growth of endocrine neoplasias, including neuroendocrine tumors of thyroid, pancreas, and adrenal (pheochromocytomas) [77][78][79].…”
Section: Mast Cells In Pathophysiology Of Hyperaldosteronismmentioning
confidence: 99%
“…Furthermore, recent studies have shown that mast cells also affect tumor growth by enhancing angiogenesis, cancer‐cell proliferation and invasion . Mast‐cell infiltration of tumors predicts poor long‐term outcomes for colorectal cancer, hepatocellular carcinoma, colorectal cancer liver metastasis, and pancreatic cancer patients . Kato et al showed that semaphorin‐4D (Sema4D), a membrane‐bound or secreted protein involved in the regulation of antitumor immunity, was demonstrated in TILs in pancreatic cancer tissue.…”
Section: Role Of Immune Cells In the Tumor Microenvironment Of Pancrementioning
confidence: 99%